Forest canopy maintains the soil community composition under elevated nitrogen deposition. (April 2020) - Liu, Tao; Mao, Peng; Shi, Leilei; Eisenhauer, Nico; Liu, Shengjie; Wang, Xiaoli; He, Xinxing; Wang, Zuyan; Zhang, Wei; Liu, Zhanfeng; Zhou, Lixia; Shao, Yuanhu; et al.
Abstract: As an important agent of environmental change, atmospheric nitrogen (N) deposition could have profound effects on terrestrial ecosystems. However, previous studies simulating N deposition in forest ecosystems were mostly based on understory manipulations, often neglecting canopy processes (e.g., N retention). Here, we employed a novel field experiment simulating N deposition through the canopy addition of N (CAN), and explored how soil nematode communities change in response to elevated N deposition in comparison with the conventional approach of understory addition of N (UAN), at two levels of N concentration. We found that 52% and 44% of the N added to the forest canopy at two N concentration levels were retained by the forest canopy. The soil nematode community showed contrasting responses to different approaches of N addition. The conventional UAN approach decreased the abundance of most nematode trophic groups and community diversity compared with CAN approach. This detrimental effect was probably due to changes in fine root biomass and/or nematode community composition caused by the high concentration of N directly entering the soils without the canopy N retention process. Our results suggest that the conventional UAN approach might result in an incomplete and potentially misleading understanding of the effects of N deposition on forest ecosystems. The results show that previous studies might have overestimated the negative effects of N deposition on forest ecosystems by overlooking forest canopy processes. In conclusion, forest canopy N-interceptions contribute to maintaining the composition of soil communities and soil biodiversity under elevated N deposition. Our study helps reconcile some of the discrepancies in the existing literature, and demonstrate the urgent need to consider canopy processes in future N deposition studies. Highlights: The approach of understory addition of N negatively affected nematode communities. Canopy addition of N seemed to have no detrimental effects on nematode communities. Canopy N-interceptions of low and high canopy N addition levels were 52% and 44%, respectively. Canopy N-interceptions can maintain soil communities under elevated N deposition.